Pelatihan E-Commerce sebagai Media Promosi Kain Songket Khas Desa Wisata Sukarara - Lalu Masyhudi; Dyah Indraswati (PENTAHELIX: Jurnal Ilmiah Pengabdian Pariwisata, 2023)
Community Service Activities (PKM) in Sukarara tourist village aim to provide skills for Songket craftsmen to be able to promote songket fabrics independently / in groups using e-commerce such as Whatsapp Business, Tiktok Shop, and Instagram. PKM is carried out in the form of training with lectures, discussion, and simulation/practice methods. PKM activities get an output in the form of songket craftsmen can apply e-commerce so that they can help promote Songket fabrics typical of Sukarara tourist village with a wider promotional reach, faster, and increasing profits. Providing new skills to the community, especially Songket craftsmen in promoting songket cloth typical of Sukarara tourism village through e-commerce.